Studi peningkatan kesejahteraan nelayan melalui program bantuan dana desa di Desa Tiga Kecamatan Tiworo Utara Kabupaten Muna Barat - Ramadan, La Ode Arif; Yusuf, Sarini; Piliana, Wa Ode (Universitas Halu Oleo, 2025)
The government has disbursed village funds for the past 5 years, but the outcomes have been inconsistent. This research seeks to understand the impact of these funds on the welfare of beneficiaries, specifically focusing on the income of fishermen in Desa Tiga, Tiworo Utara District, Southeast Sulawesi. Our findings reveal that the highest income among fishermen who received the assistance was Rp6,846,500, while the lowest was Rp2,328,111, with an average income of Rp4,382,908. Based on the welfare indicators set by the Badan Pusat Statistik 2022, the income of fishermen who received gillnet fishing gear through the village fund program in Desa Tiga places them in the prosperous category. This suggests that when village funds are used effectively, they can significantly improve the living standards of rural communities.